Famous Malaysian Indians web portal (FMIWP) / Rachel Ruran Siran - Rachel , Ruran Siran (2000)
The internet holds unimaginable amount of information. Nevertheless, resources related to Malaysian especially concerning the biographical type of information are hardly available. The biographies are of great value in that they helped to shape the future leaders of Malaysia. This report describes the proposed project on the Famous Malaysian Indians Web Portal. The Famous Malaysian lndians Web Portal is developed by a team of three members. It is a web-based biography repository. which aims to provide relevant, up-to-date and beneficial biographical resources on achievements done by the Indians community in Malaysia to all ages especially students and teachers. Each member of the team plays their own part in developing the modules for the web portal. The modules describe in this report are the Portal Enabled Knowledge Tools module, Data Manipulation module, Indexing module, Search module and Retrievel module. The development methodology used is the Waterfall with Protoryping Model, which is suitable for the project as It helps the developer gain better sense on how the user should interact with the system. Users will benefit from this web portal as it is an influential repository that is rich various multimedia contents.